Analisis Kinerja Dinas Perumahan dan Kawasan Permukiman Kota Salatiga - Ady Indriasari; Kismartini Kismartini; Sofjan Aripin (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2023)
Focus of this study aims to analyze performance through productivity, service quality, responsiveness, responsibility and accountability and pay attention to the supporting and inhibiting factors of performance at the Salatiga City Housing and Settlement Area Office. The discussion also relates to the implementation of the Government Agency Performance Accountability System (SAKIP). Descriptive qualitative research method, data collection techniques through in-depth interviews, observation and document study. Data validity checking techniques used triangulation. Research informants were determined purposively, namely internal employees, related agencies and service user communities. The results showed that the main performance at the Housing and Settlement Area Office was good but not optimal because there were several main performance achievements that had not met the targets in 2020-2021. Indications of productivity in budget limitations due to recofusing; Quality of Service has not been managed in a representative manner; Responsiveness performance found indications of some problems from external parties; Responsiveness performance in archival administrative data management is still low; Accountability performance has not managed public information optimally. Supporting factors for performance include the implementation of the main tasks and functions, the level of employee discipline, leadership style, teamwork and the support of a conducive situation in Salatiga City. Factors inhibiting performance include the limited provision of human resources and performance facilities, the phenomenon of low public awareness of the maintenance of performance results.